Cultural Convergence: The Impact of the Korean Waveon Indonesian Sociocultural Landscapes - Darmanto Darmanto; Salismi Zulfi Maulidita; Eko Nur Cahyo; Weni Laysa Nilma (SCAD Independent, 2026)
The Korean Wave (Hallyu) has emerged as a powerful global cultural phenomenon, yet its localized sociocultural implications in non-Western societies remain underexplored. This study investigated how Korean cultural products were received and adapted within Indonesian society through the lens of remote acculturation. Employing a qualitative descriptive design, secondary data were collected via the Publish or Perish (PoP) application and were visualized using VOSviewer for thematic mapping. The findings identified four major sociocultural outcomes: Korean language trends, halal-certified Korean cuisine, K-hijab (a fusion of Korean fashion and Islamic modesty), and the K-beauty phenomenon. These outcomes revealed a dominant pattern of sociocultural competence in mainstream culture, highlighting how Indonesian consumers, particularly Muslim youth, selectively adapted foreign cultural elements to fit religious and cultural norms. The study contributes to theoretical understandings of mediated cultural flows by emphasizing the outcome-oriented nature of remote acculturation and its role in shaping identity, lifestyle, and consumer behavior in multicultural contexts. It also offers practical implications for cross-cultural communication, soft power strategies, and culturally sensitive product adaptation in global markets.